New Mutant Mouse with Skeletal Deformities Caused by Mutation in Delta Like 3 (Dll3) Gene - TSUJI, Takehito; KUNIEDA, Tetsuo; SHINKAI, Yusuke; KAWAMOTO, Yasuo (Experimental Animals, 2004)
We have established a new mouse strain with vertebral deformities caused by an autosomal single recessive mutation (oma). The mutant mice showed short trunk and short and kinky tail. The skeletal preparations of newborn and prenatal mice showed disorganized vertebrae and numerous vertebral and rib fusions which are thought to be caused by patterning defects at the stage of somitegenesis. Linkage analysis localized the oma locus on the proximal region of mouse chromosome 7 close to Dll3 gene. Dll3 is the gene involved in the Notch signaling pathway and null-mutation of the gene has been reported to cause vertebral deformities. The phenotypic similarity between oma and Dll3 null-mutant mice suggests that the causative gene for the oma mutant is the Dll3 gene. We, therefore, investigated the nucleotide sequence of the Dll3 gene of the oma mouse and found a single nucleotide substitution of G to T which causes missense mutation of glycine to cysteine at codon 409. Since the amino acid substitution is a nonconservative amino acid substitution at the conserved portion of the Dll3 protein, and the substitution is specific to the mutant mice, we concluded that the nucleotide substitution of the Dll3 gene is responsible for the skeletal deformities of the oma mouse.